The top 100 most cited articles in the past 30 years of wheat allergy: a bibliometric analysis - Zhan, Mengyuan; Hou, Yibo; Wen, Liping; Xu, Tengda (Frontiers in Immunology, 2024)
Abstract Background: Wheat allergy（WA）, characterized by immunological responses to wheat proteins, is a gluten-related disorder that has become increasingly recognized in recent years. Bibliometrics involves the quantitative assessment of publications within a specific academic domain. Objectives: We aimed to execute an extensive bibliometric study, focusing on the past 30 years of literature related to wheat allergy. Methods: We searched the Web of Science database on 5th Dec 2023. We used the keywords “wheat allergy or wheat anaphylaxis or wheat hypersensitivity,”“gliadin allergy or gliadin anaphylaxis or gliadin hypersensitivity,”“wheat-dependent exercise-induced anaphylaxis,” and “baker's asthma” for our search. All items published between 1993 and 2023 were included. The top 100 most cited articles were identified and analyzed. Results: Our study conducted an in-depth bibliometric analysis of the 100 most-cited articles in the field of wheat allergy, published between 2002 and 2019. These articles originated from 20 different countries, predominantly Japan and Germany. The majority of these articles were centered on the pathogenesis and treatment of wheat allergy (WA). The Journal of Allergy and Clinical Immunology (JACI) was the most prolific contributor to this list, publishing 14 articles. The article with the highest citation count was published by Biomed Central (BMC) and garnered 748 citations. The peak citation year was 2015, with a total of 774 citations, while the years 1998, 2001, and 2005 saw the highest publication frequency, each with 7 articles. Conclusions: Our study aims to provide physicians and researchers with a historical perspective for the scientific progress of wheat allergy, and help clinicians effectively obtain useful articles that have a significant impact on the field of wheat allergy.